To solve the inequality \( x - \frac{1}{3} \leq \frac{1}{2} \), we will first isolate \( x \).
- Add \( \frac{1}{3} \) to both sides:
\[ x \leq \frac{1}{2} + \frac{1}{3} \]
- To add \( \frac{1}{2} \) and \( \frac{1}{3} \), we need a common denominator. The least common multiple of 2 and 3 is 6. So we can convert the fractions:
\[ \frac{1}{2} = \frac{3}{6} \quad \text{and} \quad \frac{1}{3} = \frac{2}{6} \] So now we add them:
\[ x \leq \frac{3}{6} + \frac{2}{6} = \frac{5}{6} \]
Thus, the solution to the inequality is:
\[ x \leq \frac{5}{6} \]
The correct response is: x less-than-or-equal-to Start Fraction 5 over 6 End Fraction.